Rasionalitas Penggunaan Hak Suara Pemilih Pemula Kota Surabaya dalam Pemilihan Umum Presiden dan Wakil Presiden 2024 - Winokan, Zafran Syafiq Shobha; Iqbal, Muhammad Falih; Fauzi, Agus Machfud (Jurnal Politikom Indonesiana, 2024)
This research aims to identify the rationality of first-time voters’ use of their voting rights in Surabaya during the 2024 presidential and vice-presidential elections. The study employs a qualitative approach with a descriptive phenomenological method. Data collection was conducted through observation, in-depth interviews, and supported by literature studies sourced from journals, books, theses, and other relevant documents related to the research objectives. Max Weber’s theory of rationality is used in this study as an analytical tool, as it seeks to understand the basis of individual actions through several ideal stages. The findings indicate that the rationality behind first-time voters’ use of their voting rights in Surabaya is based on personality aspects, education, achievements, vision and mission, track record, work programs, and proficiency in language, while tending to ignore the religious, racial, ethnic, gender, and cultural backgrounds of each presidential and vice-presidential candidate. The obstacles and challenges that presidential and vice-presidential candidates must face in the 2024 elections include declining public trust in the government, the complexity of social issues in Indonesia since the Covid-19 pandemic, and advancements in Science and Technology (IPTEK). Keywords: Rationality, Novice Voters, Voting Rights, General Elections